Meningkatkan Pengetahuan Keluarga Pasien pada Pelayanan di IGD dengan Edukasi Pemilihan TRIAGE: Increasing the knowledge of patient families regarding services in the emergency room with TRIAGE selection education - Sahat Tua Naibaho, Beres; Widyowati, Agustin (Chakra Brahmanda Lentera Institute, 2025)
The TRIAGE process affects the response time of medical personnel in the emergency department, which varies according to the patient's priorities. Inaccurate TRIAGE assessments can increase the risk of morbidity, affect treatment outcomes, and affect the length of time a patient stays in the emergency room. This community service aims to increase Patients' Family Knowledge in Services at the Emergency Room which is carried out by providing TRIAGE Election Education. This community service activity was held on February 9, 2024 at the Emergency Room of Karo Regency Hospital. This community service activity consists of 3 stages of activities, namely the first stage of preparation, the second stage of implementation and the third stage of evaluationii. Participants were 12 people who were given a questionnaire about the services in the emergency room before and after being given TRIAGE Election Education. The results stated that after being given TRIAGE Election Education, the level of family knowledge related to services in the emergency room was mostly 58.3% good. TRIAGE Selection Education can Increase Patients' Family Knowledge on Services in the Emergency Room.